Prevention of cardiovascular diseases in women in Europe - Rynkiewicz, Andrzej (Menopause Review/Przegląd Menopauzalny, 2008)
Sixty years after the scientific background of the pelvic floor muscle rehabilitation has been described by Arnold Kegel, this method undergoes a renaissance giving many patients an opportunity to fight such important health problems as pelvic organ prolapse and/or urinary incontinence. This paper reviews the published up-to-date data on the role of pelvic floor muscle exercise in modern gynecological practice.